2020
DOI: 10.1007/s10111-020-00658-5
|View full text |Cite
|
Sign up to set email alerts
|

Do drivers change their manual car-following behaviour after automated car-following?

Abstract: There is evidence that drivers’ behaviour adapts after using different advanced driving assistance systems. For instance, drivers’ headway during car-following reduces after using adaptive cruise control. However, little is known about whether, and how, drivers’ behaviour will change if they experience automated car-following, and how this is affected by engagement in non-driving-related tasks (NDRT). The aim of this driving simulator study, conducted as part of the H2020 L3Pilot project, was to address this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…They were also asked not to overtake the lead vehicle, but otherwise, follow the normal rules of the road, ensuring the safe operation of the vehicle, and maintaining their desired distance from the lead vehicle. After each experimental drive, the participants were given a 10-min break, during which they were asked to complete a set of questionnaires, including Arnett's Sensation Seeking Questionnaire (Arnett, 1994), traffic locus of control ( Özkan & Lajunen, 2005) and the Driver Style Questionnaire (French et al, 1993), see Louw et al (2020). However, results from these questionnaires are not reported here, since they did not include questions about driver workload.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were also asked not to overtake the lead vehicle, but otherwise, follow the normal rules of the road, ensuring the safe operation of the vehicle, and maintaining their desired distance from the lead vehicle. After each experimental drive, the participants were given a 10-min break, during which they were asked to complete a set of questionnaires, including Arnett's Sensation Seeking Questionnaire (Arnett, 1994), traffic locus of control ( Özkan & Lajunen, 2005) and the Driver Style Questionnaire (French et al, 1993), see Louw et al (2020). However, results from these questionnaires are not reported here, since they did not include questions about driver workload.…”
Section: Methodsmentioning
confidence: 99%
“…However, participants' subjective ratings of riskiness due to the THW maintained by the vehicle was also dependent on environmental factors such as visibility (fog), and traffic conditions such as following a truck, with driver discomfort increasing with lower visibility, increased traffic, and when following a truck, as opposed to a car. In Louw et al (2020), we observed, via subjective ratings, that shorter headways maintained by HAD are perceived as riskier or unsafe by drivers, especially when they are not in control of the driving task. Resuming control from automation in the presence of a closer lead vehicle is also likely to be more demanding, especially following engagement in an NDRT (Mehler et al, 2009), further exacerbating the OOTL effect, with studies on HAD showing that engagement in NDRTs increases driver workload, and negatively affects their driving performance after takeovers (Du et al, 2020;Wandtner et al, 2018;Zeeb et al, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…Estimates can vary greatly depending on the country and region, so many experimental studies report high concentrations of pollutants on roads with a large number of diesel vehicles. It was found that a small part of dirty vehicles, for example, with outdated emission standards, high mileage, or failures in engine emission control systems, can be characterised by more significant emissions than the rest [17]. Driving conditions can affect the quality of roadside air in two ways, namely the level of emissions and turbulence caused by the vehicle.…”
Section: Resultsmentioning
confidence: 99%
“…Monitoring the environment but not being in physical control of the vehicle is defined as the “on-the-loop” state. Due to the expectation for the driver to resume manual control while in CAD and shift to an “in-the-loop” state from an “on-the-loop” or “out-of-the-loop” state, a significant portion of the human factors research focused on the higher levels of driving automation systems has focused on the resumption of manual control ( Seppelt and Victor, 2016 ; Louw et al, 2020 ). In contrast, there has been limited research on how drivers respond to evasive maneuvers initiated by a CAD vehicle.…”
Section: Introductionmentioning
confidence: 99%